INDUSTRIAL IOT, FACTORY OF THINGS - Shkoda, Viktor (Nazarbayev University School of Engineering and Digital Sciences, 2024)
This capstone project investigates the optimization of the MCP2515 CAN bus module for intra-vehicle communications in smart automotive systems. Employing Arduino-based prototypes, the study explores the impact of varying SPI clock speeds and transmission delays on the system's efficiency and reliability. Through experimental trials, the research evaluates how different settings influence the throughput and channel utilization of the CAN network, focusing on clock speeds of 5MHz and 2.5MHz. Results indicate that specific configurations significantly enhance communication effectiveness, showcasing an optimal balance of speed and stability. This study not only provides a detailed understanding of the CAN bus capabilities but also offers valuable insights for automotive engineers seeking to improve the safety and functionality of modern vehicles through advanced communication technologies.
Keywords: IoT; CAN BUS; Arduino; Type of access: Open access